Coverage of Literacy Teaching of Students with Mental Development Problems in the Scientific Literature (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article is aimed at highlighting in scientific literature one of the important tasks of world education - the formation of the personality of a functionally literate student.